Implementasi Model Astradharmakarya dalam Wayang Orang Bocah: Studi Pre–Post Internalisasi Nilai Etika - Chrisnar Bagas Pamungkas (LPPM UNS, 2026)
This research aims to evaluate the effectiveness of the Astradharmakarya for Character (A4C) model in internalizing ethical values in children through the Wayang Orang Bocah (WOB) activities at Sanggar Soerya Soemirat, Surakarta. The research subjects include child performers of WOB, trainers, and parents. The method used is descriptive qualitative with an ethnographic case study design, employing participant observation, in-depth interviews, and documentation. The ethnographic approach was chosen due to its suitability for understanding traditional arts as culturally based pedagogical practices.The novelty of this study lies in the empirical verification of the A4C model through pre–post evaluations, as well as the integration of dharma values with the aesthetics of wiraga–wirama–wirasa as the foundation of character education. The findings show that the creative process in WOB can enhance children’s discipline, responsibility, politeness, cooperation, and emotional regulation, while also positioning traditional arts as a medium for internalizing moral values.Keywords: Astradharmakarya, Wayang Orang Bocah, character education.